Calcium-binding proteins are altered in the cerebellum in schizophrenia - Vidal-Domènech, Francisco; Riquelme, Gemma; Pinacho, Raquel; Rodriguez-Mias, Ricard; Vera, América; Monje, Alfonso; Ferrer, Isidre; Callado, Luis F.; Meana, J. Javier; Villén, Judit; Ramos, Belén (PloS one, 2020)
Alterations in the cortico-cerebellar-thalamic-cortical circuit might underlie the diversity of symptoms in schizophrenia. However, molecular changes in cerebellar neuronal circuits, part of this network, have not yet been fully determined. Using LC-MS/MS, we screened altered candidates in pooled grey matter of cerebellum from schizophrenia subjects who committed suicide (n = 4) and healthy individuals (n = 4). Further validation by immunoblotting of three selected candidates was performed in two cohorts comprising schizophrenia (n = 20), non-schizophrenia suicide (n = 6) and healthy controls (n = 21). We found 99 significantly altered proteins, 31 of them previously reported in other brain areas by proteomic studies. Transport function was the most enriched category, while cell communication was the most prevalent function. For validation, we selected the vacuolar proton pump subunit 1 (VPP1), from transport, and two EF-hand calcium-binding proteins, calmodulin and parvalbumin, from cell communication. All candidates showed significant changes in schizophrenia (n = 7) compared to controls (n = 7). VPP1 was altered in the non-schizophrenia suicide group and increased levels of parvalbumin were linked to antipsychotics. Further validation in an independent cohort of non-suicidal chronic schizophrenia subjects (n = 13) and non-psychiatric controls (n = 14) showed that parvalbumin was increased, while calmodulin was decreased in schizophrenia. Our findings provide evidence of calcium-binding protein dysregulation in the cerebellum in schizophrenia, suggesting an impact on normal calcium-dependent synaptic functioning of cerebellar circuits. Our study also links VPP1 to suicide behaviours, suggesting a possible impairment in vesicle neurotransmitter refilling and release in these phenotypes.